Empowering older persons: The truths and challenges of care decisions for enhanced quality of life - Fenech, Maria Aurora (Magyar Gerontológia, 2024)
As the global population ages, empowering older persons in care decisions becomes increasingly crucial for enhancing their quality of life. This paper explores the complexities of empowerment in the context of care decisions for older persons, examining both the facts and challenges involved.